ANSWER
![y = 2x -4](https://img.qammunity.org/2020/formulas/mathematics/college/r6mhq20n7hk1p45l6ryo8e2hcoe7qf0saq.png)
Step-by-step explanation
Part a)
Eliminating the parameter:
The parametric equation is
![x = 5 + ln(t)](https://img.qammunity.org/2020/formulas/mathematics/college/o7ssuixwnfskmyn11cp9hkvvducll6c00g.png)
![y = {t}^(2) + 5](https://img.qammunity.org/2020/formulas/mathematics/college/udmhww9taq06pwyfakkq9birhjgbodmjm3.png)
From the first equation we make t the subject to get;
![x - 5 = ln(t)](https://img.qammunity.org/2020/formulas/mathematics/college/c9wi2oy3o87cu2icmu682yl5xant3t55ka.png)
![t = {e}^(x - 5)](https://img.qammunity.org/2020/formulas/mathematics/college/wj01egrlggo9flulcdp1zs9eblwouok14f.png)
We put it into the second equation.
![y = { ({e}^(x - 5)) }^(2) + 5](https://img.qammunity.org/2020/formulas/mathematics/college/pi30q1ollag67itgs5tdzbbwfmnwekodmb.png)
![y = { ({e}^(2(x - 5))) } + 5](https://img.qammunity.org/2020/formulas/mathematics/college/db1kkbmfdy0wmn1z95z1y518rvwz20s8mu.png)
We differentiate to get;
![(dy)/(dx) = 2 {e}^(2(x - 5))](https://img.qammunity.org/2020/formulas/mathematics/college/amhcv2dslxz1px5sbs7uz5tno3rohlymjy.png)
At x=5,
![(dy)/(dx) = 2 {e}^(2(5 - 5))](https://img.qammunity.org/2020/formulas/mathematics/college/fmhk2eem07nvflcbkvr2u82hivjdfs1k5b.png)
![(dy)/(dx) = 2 {e}^(0) = 2](https://img.qammunity.org/2020/formulas/mathematics/college/jibjotzk7av7njd9ou0i6q4v041y7wsr8i.png)
The slope of the tangent is 2.
The equation of the tangent through
(5,6) is given by
![y-y_1=m(x-x_1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lwv5ftdd36i4idvu50qxfdgwxhdby4wlt5.png)
![y - 6 = 2(x - 5)](https://img.qammunity.org/2020/formulas/mathematics/college/c2c3talj2n0vnkvwwuuro8p62rie2cjnkw.png)
![y = 2x - 10 + 6](https://img.qammunity.org/2020/formulas/mathematics/college/qg6qvvn418jivomsc5lj8o2qdbksv7utzn.png)
![y = 2x -4](https://img.qammunity.org/2020/formulas/mathematics/college/r6mhq20n7hk1p45l6ryo8e2hcoe7qf0saq.png)
Without eliminating the parameter,
![(dy)/(dx) = ( (dy)/(dt) )/( (dx)/(dt) )](https://img.qammunity.org/2020/formulas/mathematics/high-school/oc4ti5okj2p6w2c427gar650l5eq42jyww.png)
![(dy)/(dx) = ( 2t)/( (1)/(t) )](https://img.qammunity.org/2020/formulas/mathematics/college/6fvkadd8ofeodazkw55y6bi57rhm0i6lab.png)
![(dy)/(dx) = 2 {t}^(2)](https://img.qammunity.org/2020/formulas/mathematics/college/k8h0xcprt3eenggkwqgrmulvj4u6q49iji.png)
At x=5,
![5 = 5 + ln(t)](https://img.qammunity.org/2020/formulas/mathematics/college/ha061mqhad4obm4e4voit7vx3jbm1ws0vx.png)
![ln(t) = 0](https://img.qammunity.org/2020/formulas/mathematics/college/a5m1991waxcks7dvjcjrdjgylbvqwj5scr.png)
![t = {e}^(0) = 1](https://img.qammunity.org/2020/formulas/mathematics/college/aojd3a2dq4oej6hj5j52y93uel7ktj5hl8.png)
This implies that,
![(dy)/(dx) = 2 {(1)}^(2) = 2](https://img.qammunity.org/2020/formulas/mathematics/college/2mgg5nv85px87arbba4r80dfirjxqpu20e.png)
The slope of the tangent is 2.
The equation of the tangent through
(5,6) is given by
![y-y_1=m(x-x_1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/lwv5ftdd36i4idvu50qxfdgwxhdby4wlt5.png)
![y - 6 = 2(x - 5) =](https://img.qammunity.org/2020/formulas/mathematics/college/q0hq5vrsbuq1eqx8pe06ahezuv7fiq9q85.png)
![y = 2x -4](https://img.qammunity.org/2020/formulas/mathematics/college/r6mhq20n7hk1p45l6ryo8e2hcoe7qf0saq.png)